2021
DOI: 10.1002/ajhb.23605
|View full text |Cite
|
Sign up to set email alerts
|

No association between adult sex steroids and hand preference in humans

Abstract: Background: There is ongoing debate about the effects of hormones on the lateralization of the developing brain. In humans, there are conflicting theories of how testosterone during development should affect lateralization. Empirical studies linking prenatal and postnatal testosterone levels to hand preference (a proxy for lateralization) are similarly mixed. Links between hand preference and health may also suggest a mediating role of steroid hormones such as testosterone and estradiol. Studies to date of adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The delay in the development of the left hemisphere will result in a compensatory growth of the right hemisphere's homolog regions, increasing the incidence of left-handedness (Beking et al, 2018;Geschwind & Galaburda, 1985). Although this theory has been challenged (e.g., Bryden et al, 1994;Richards, Medland et al, 2021;Richardson, 2022), there is some evidence supporting testosterone's influence on lateralization. For example, Lust et al (2011) found that a high level of prenatal testosterone is related to a weaker handedness and stronger cerebral dominance for language among 6-year-old children.…”
Section: Sex Hormones: Androgens Estrogens and Progestogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The delay in the development of the left hemisphere will result in a compensatory growth of the right hemisphere's homolog regions, increasing the incidence of left-handedness (Beking et al, 2018;Geschwind & Galaburda, 1985). Although this theory has been challenged (e.g., Bryden et al, 1994;Richards, Medland et al, 2021;Richardson, 2022), there is some evidence supporting testosterone's influence on lateralization. For example, Lust et al (2011) found that a high level of prenatal testosterone is related to a weaker handedness and stronger cerebral dominance for language among 6-year-old children.…”
Section: Sex Hormones: Androgens Estrogens and Progestogensmentioning
confidence: 99%
“…Although it remains unclear how sex hormones can be involved in functional lateralization, it is hypothesized that they may influence interhemispheric connection affecting the interaction/inhibition between the two hemispheres (for review see Hausmann, 2017). It is noteworthy that recent evidence showed an absence of an association between female sex hormones and hand preference (Richardson, 2022).…”
Section: Sex Hormones: Androgens Estrogens and Progestogensmentioning
confidence: 99%